Association between plasma odd-chain fatty acid levels and immune cell traits in psoriasis: insights from a prospective cohort study - Shi, Rongcan; Xu, Yifei; Jiang, Xingyu; Yu, Bo; Ma, Rui; Wang, Xin; Shi, Yuling (Frontiers in Immunology, 2025)
Background/ObjectivesPsoriasis is a chronic, immune-mediated skin disease frequently linked to metabolic dysregulation. Odd-chain fatty acids (OCFAs), a group of bioactive lipids, have been implicated in inflammation and metabolic health; however, their role in psoriasis remains poorly defined. This study aimed to investigate the associations between plasma OCFA levels, white blood cell (WBC) traits, and psoriasis severity.MethodsA total of 235 patients with moderate-to-severe plaque psoriasis were enrolled from the Shanghai Psoriasis Effectiveness Evaluation CoHort. Baseline plasma OCFA concentrations were measured using gas chromatography–mass spectrometry, and routine hematologic parameters were extracted from clinical records. Psoriasis severity was assessed using the Psoriasis Area and Severity Index, Body Surface Area, Dermatology Life Quality Index, and the Hospital Anxiety and Depression Scale for Anxiety and Depression. Therapeutic response was evaluated at weeks 12 and 28 based on clinical improvement. Multivariate linear and logistic regression analyses, stratified subgroup analyses, and restricted cubic spline models were employed.ResultsHigher plasma levels of C15:0 were significantly associated with increased total WBC and neutrophil counts. C17:0 levels were positively associated with WBC counts among females and older adults, and inversely associated with eosinophil counts in females and individuals with normal BMI. Additionally, C17:1n7 levels were positively associated with lymphocyte and monocyte counts. Total OCFA levels were also positively associated with overall WBC and neutrophil counts. These associations varied by sex, age, BMI, smoking and alcohol consumption history, and the presence of comorbidities such as psoriatic arthritis, hypertension, and type 2 diabetes. While no significant associations were observed between plasma OCFA levels and psoriasis severity or treatment response in the overall cohort, stratified analyses revealed potential relationships in specific subgroups.ConclusionsPlasma OCFAs are differentially associated with circulating immune cell profiles in patients with psoriasis, suggesting a potential immunomodulatory role. Although OCFAs were not linked to overall disease severity or short-term treatment outcomes, subgroup-specific associations indicate their relevance in particular clinical phenotypes. These findings highlight the need for further longitudinal studies to clarify the role of OCFAs in immune regulation, disease progression, and comorbidity management in psoriasis.